Evaluation of the acceptability of point of care diagnostic test for prenatal toxoplasmosis (translational research phase III) - Juan Camilo Londoño-Martinez; Stefany Velasco-Velasquez; Sara Cordero-Lopez; María Fernanda Osorio; Daniel Celis-Giraldo; Juliette Thibodeau; Isabelle Baird; Rima McLeod; Jorge Gomez-Marin (Journal of Infection and Public Health, 2023)
Background: A new point of care test (POC) was developed that is promising as a tool to enhance impact of prenatal care programs for toxoplasmosis, however, no reports exist about its use or acceptability for healthcare personnel and mothers in Colombia. Methods: This was a translational research - phase III study of the acceptability of a new POC test (Toxoplasma ICT IgG-IgM, LDBio) for qualitative diagnosis of toxoplasmosis in 783 pregnant women and 30 health personnel in primary health care sites in the city of Armenia, Quindío (Colombia). Along with collection of the results of diagnostic POC and confirmatory test and demographic information, we evaluated acceptability through measure of the willingness, credibility, and satisfaction by using questionnaires with a Likert scale during routine prenatal care visits. Results: POC positivity was 46.5% among pregnant participants and was significantly related to socioeconomic factors, including education level (p = 0.00000000) and insurance status (p = 0.00000015). A total of 93–97% of healthcare personnel indicated agreement to positive statements regarding total satisfaction and total credibility of the LDBio test, but qualitative questions identified “Difficulty in the test procedure” as the most common response about barriers to apply the test. Greater than 90% of pregnant participants agree that POC test should be routine for all pregnant woman and permanently implemented. Conclusions: The test had near complete acceptability. In future studies it is necessary to examine the effect of non-differentiation between IgG and IgM isotypes.